Тепловой контроль корундовой керамики: классические методики при оптическом нагреве; Дефектоскопия; № 7 - Черных С. Е. Сергей Евгеньевич; Вавилов В. П. Владимир Платонович; Костин В. Н. Валерий Николаевич; Комоликов Ю. И. Юрий Игоревич; Кладов Д. Дмитрий (2024, 2024)
Заглавие с экрана